Environmental Preferences and Concerns of Recreational Trail Runners - Rosenkrantz, Leah; Schuurman, Nadine; Lear, Scott A. (International journal of environmental research and public health, 2024)
Trail running is a fast-growing sport, linked to improvements in both physical and psychological well-being. Despite its popularity, the preferences of trail runners are not well known. The objective of this study was to examine the environmental preferences and concerns of trail runners with respect to age and gender. We conducted a cross-sectional survey of recreational trail runners. A total of 548 people responded, of which 50.1% of respondents were women and 44.2% were men. The sample was distributed relatively evenly across age groups, up to 54 years; respondents over 55 represented only 9.4% of the sample. Comparisons of runner characteristics by gender indicated significant differences (p < 0.05) according to age, distance run per week, and number of days run per week. Certain runner preferences also differed significantly by gender, including importance of running around others, the type of trail races they seek, and whether or not they like to seek “vert” or elevation in their runs. Major concerns for both genders while running included lack of cell reception (Men: 33.8%; Women: 50.8%) and getting lost (Men: 26.8%; Women: 35.5%). Comparisons of the results of this study help to strengthen our understanding of trail runners’ environmental preferences and concerns and can be used to guide future design and maintenance of trail environments to encourage greater participation in the sport.